2020
DOI: 10.3389/fpls.2020.549636
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Critical Nitrogen Dilution Curve for Winter Wheat to Diagnose Nitrogen Status Under Different Nitrogen and Irrigation Rates

Abstract: Modified Critical Nitrogen Dilution Curve for constructing mN c dilution curves under different water and N fertilizer management. Due to the significant differences in hereditary, CO fixation efficiency and N metabolism pathways for C 3 and C 4 crops, the construction of mN c dilution curve suitable for different N response mechanisms will be conducive to the sustainable N management in crop plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Most N c dilution curves fitted for organ biomass and LAI bases are different, reflecting the effect of G × E × M interaction. This implies that changes of wheat genotypes, planting environment, and management can affect the curve parameters, leading to potential errors in crop N nutrition status diagnosis and N demand estimations [ 28 , 39 , 40 ]. The uncertainty of the fitted parameter A 1 was significantly less than that of parameter A 2 , indicating that the curve parameter A 1 for organ basis was less affected by G × E × M. The organ-specific N c dilution curves showed that the N concentration in the leaf for all experiments was higher than in the stem (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most N c dilution curves fitted for organ biomass and LAI bases are different, reflecting the effect of G × E × M interaction. This implies that changes of wheat genotypes, planting environment, and management can affect the curve parameters, leading to potential errors in crop N nutrition status diagnosis and N demand estimations [ 28 , 39 , 40 ]. The uncertainty of the fitted parameter A 1 was significantly less than that of parameter A 2 , indicating that the curve parameter A 1 for organ basis was less affected by G × E × M. The organ-specific N c dilution curves showed that the N concentration in the leaf for all experiments was higher than in the stem (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Winter wheat is a typical crop with a long growth cycle, large differences in AGB during the different growth stages, and significant nitrogen “dilution” effects, which in turn produce large differences in the time series of AGB and PNC (Justes et al, 1994; Zhao et al, 2020). The leaf-related parameters are like the VI in the phenological stage, which is consistent with previous studies (Zhao et al, 2021; Feng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 gives the number of samples collected in each experiment. The measurement methods and equations for calculating AGB, LGB, PNC, LNC, and LAI are the same as used by Zhao et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Many critical N concentration dilution curve models have been established for pepper [ 14 ], wheat [ 15 ], maize [ 16 ], cotton [ 17 ], winter oilseed rape [ 18 ], and tomatoes [ 19 ]. Nitrogen-deficit accumulation modeling based on critical nitrogen concentration curves is an effective method for the nitrogen nutritional diagnosis of crops [ 16 , 20 ]. Currently, most of the research on critical N concentration modeling focuses on the status of nitrogen gain or loss and utilization in facility crops under different water and fertilizer conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%